Pemanfaatan Limbah Batang Pisang sebagai Alternatif Pakan Ternak Melalui Uji Kualitas Fisik Pakan - Jati, Putri Zulia; Novita, Maulina; Setiawan, Bagus Dimas (Indo Green Journal, 2024)
The potential of banana stems has not been utilized optimally due to the low nutritional content, so it is necessary to add MA11 inoculum for further processing by anaerobic fermentation or silage. This research aims to determine the physical quality of Batang Pisang fermentation silage waste using MA11 inoculum. This research used a completely randomized design consisting of 4 treatments, each treatment unit repeated 4 times. P0 = Banana Bar + MA-11 0%, P1 = Banana Bar + MA-11 2%, P2 = Banana Bar + MA-11 4%, P3 = Banana Bar + MA-11 6%. The variables measured are color, texture, pH and aroma. The data obtained were analyzed based on various analyzes carried out using the Duncan test at 5% and 1% levels. The results of this research show that it has an effect on color, texture, pH and aroma. It was concluded that the color of the silage produced was blackish brown. The pH of the silage produced for P0, P1, P2 and P3 respectively is 5.4-5.8, which means the pH produced is poor. The texture of the resulting silage is slightly soft (a bit lumpy, contains mucus). The resulting aroma is not sour and not rotten.